Fluvastatin in the first-line therapy of acute coronary syndrome: results of the multicenter, randomized, double-blind, placebo-controlled trial (the FACS-trial) - Ostadal, Petr; Alan, David; Vejvoda, Jiri; Kukacka, Jiri; Macek, Milan; Hajek, Petr; Mates, Martin; Kvapil, Milan; Kettner, Jiri; Wiendl, Martin; Aschermann, Ondrej; Slaby, Josef; et al. (Trials, 2010)
BACKGROUND: Statins have been proved to be effective in reduction of mortality and morbidity when started in the early secondary prevention in stabilized patients after acute coronary syndrome (ACS). The safety and efficacy of statin administration directly in the first-line therapy in unstable ACS patients is not clear. The aim of our study was, therefore, to assess the effect of statin treatment initiated immediately at hospital admission of patients with ACS. METHODS: The trial was stopped prematurely after enrollment of one hundred and fifty-six patients with ACS that were randomized at admission to fluvastatin 80 mg (N = 78) or placebo (N = 78). Study medication was administered immediately after randomization and then once daily for 30 days; all patients were then encouraged to continue in open-label statin therapy and at the end of one-year follow-up 75% in the fluvastatin group and 78% in the placebo group were on statin therapy. RESULTS: We did not demonstrate any difference between groups in the level of C-reactive protein, interleukin 6, and pregnancy-associated plasma protein A on Day 2 and Day 30 (primary endpoint). Fluvastatin-therapy, however, significantly reduced one-year occurrence of major adverse cardiovascular events (11.5% vs. 24.4%, odds ratio (OR) 0.40, 95% CI 0.17-0.95, P = 0.038). This difference was caused mainly by reduction of recurrent symptomatic ischemia (7.7% vs. 20.5%, OR 0.32, 95% CI 0.12-0.88, P = 0.037). CONCLUSIONS: This study failed to prove the effect of fluvastatin given as first-line therapy of ACS on serum markers of inflammation and plaque instability. Fluvastatin therapy was, however, safe and it may reduce cardiovascular event rate that supports immediate use of a statin in patients admitted for ACS. TRIAL REGISTRATION: NCT00171275.
Keywords: senioři; dvojitá slepá metoda; placebo efekt; C-Reactive Protein; Pregnancy-Associated Plasma Protein-A; kyseliny mastné mononenasycené; Indoles; Sample Size; Placebo Effect; Double-Blind Method; interleukin-6; mediátory zánětu; Interleukin-6; Time Factors; Česká republika; příjem pacientů; výsledek terapie; C-reaktivní protein; Kaplan-Meier Estimate; Middle Aged; Drug Administration Schedule; Risk Assessment; mužské pohlaví; Kaplanův-Meierův odhad; Prospective Studies; Patient Selection; fluvastatin; Inflammation Mediators; Czech Republic; Secondary Prevention; výběr pacientů; Hydroxymethylglutaryl-CoA Reductase Inhibitors; těhotenský plazmatický protein A; ženské pohlaví; hodnocení rizik; Humans; prospektivní studie; statiny; Early Termination of Clinical Trials; Fluvastatin; odds ratio; Chi-Square Distribution; časové faktory; Fatty Acids, Monounsaturated; lidé středního věku; rozdělení chí kvadrát; předčasné ukončení klinických zkoušek; rozvrh dávkování léků; sekundární prevence; indoly; akutní koronární syndrom; Patient Admission; Female; Aged; Treatment Outcome; Acute Coronary Syndrome; velikost vzorku; lidé; Male; Odds Ratio